Effect of Splitter Angles on Characteristics of Mixing Layer Flow: A Numerical Study - Trung Dung Nguyen; Dinh Anh Le; Van Minh Do; Anh Tuan Nguyen; The Hung Tran (Journal of Applied and Computational Mechanics)
This study investigates the effect of splitter angles on the aerodynamic flow of two free streams under incompressible conditions. The angle of the splitter is changed from 0 to 40° to simulate different wake structures on the slant. The convective Mach number was selected at 0.185. The velocities at the upper surface (primary freestream) and lower surface (secondary freestream) are changed to generate two different cases. The simulation was conducted using steady generalized k-ω (GEKO) models with modification of mixing coefficients and large eddy simulation for transient flows. The results of numerical data were validated with experimental data with the same flow conditions. This study presents that when initial parameters are suitably selected, the numerical schemes provide sufficient accurate averaged results. For case 1, when the primary freestream is higher, the length of the mixing region increases with the splitter angle. Additionally, the generation of the wake flow leads to movement upward of the mixing position for splitter angles above 20°. For case 2, when the primary freestream is smaller, the mixing characteristics are little changed for different angles. The Proper Orthogonal Decomposition (POD) was applied for case 1 and the results showed that the pair of counter-vortices is the main dominant structure flow in the mixing region. The averaged flow fields, turbulent kinetic energy, and unsteady behavior were analyzed and discussed insight in this study.